b - Blackford, Harriet (London : Collins, 2015)
We know we all need to eat, but why do we need to and where does it go? Filled with photos and clear diagrams, follow the food you eat on its journey through your body and find out what happens to it along the way.
Translation of: The digestive system.
Title supplied by OCLC WorldCat.
Text in Arabic.
Keywords: Arabic language materials; Digestive organs -- Juvenile literature; Digestion